Behavioral change and socio-economic impact from charcoal producers to eco-friendly coffee farmers in Jatiarjo Village, Prigen, Pasuruan, Indonesia - Wibisono, Mulyono; Nugroho, Agung Murti; Prabandari, Sri Palupi (Fakultas Pertanian Universitas Yudharta Pasuruan, 2024)
Introduction: The transition from traditional charcoal production to sustainable coffee farming in Jatiarjo Village, Prigen, Pasuruan, Indonesia, highlights a critical effort to achieve environmental sustainability and improve socio-economic conditions. This study explores behavioral changes and socio-economic impacts while integrating eco-friendly agricultural practices, providing a model for similar transformations globally. Methods: A mixed-methods approach was used, combining quantitative data from local economic reports with qualitative insights from interviews and focus group discussions with farmers and stakeholders. SWOT analysis (using IFAS and EFAS frameworks) was employed to identify key strengths, weaknesses, opportunities, and threats shaping the transition. Results: Findings indicate that Jatiarjo Village benefits from internal strengths, such as fertile land, traditional agricultural knowledge, and strategic partnerships. These are complemented by external opportunities, including global demand for sustainable coffee and supportive government policies. Quantitative analysis shows significant increases in household income and biodiversity, while qualitative data highlight enhanced community resilience and environmental stewardship. However, barriers like inadequate infrastructure, dependence on external funding, and climate risks persist. Literature supports these findings, emphasizing the importance of community engagement, institutional support, and capacity building in achieving sustainable rural development. Conclusion: Jatiarjo Village's transition showcases how rural communities can align environmental and economic goals through eco-friendly coffee farming. By addressing socio-economic challenges and leveraging community strengths, this initiative provides actionable insights for scaling sustainable agricultural practices globally. Future research should focus on quantifying long-term socio-economic impacts and exploring adaptive strategies to mitigate climate and market risks.